1996
DOI: 10.1182/blood.v87.4.1385.bloodjournal8741385
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-granule membrane mirrors the platelet plasma membrane and contains the glycoproteins Ib, IX, and V

Abstract: We have recently shown that several components from the platelet plasma membrane were also present at different rates in the alpha-granule membrane. This is the case for the glycoprotein (GP) IIb-IIIa (CD41), CD36, CD9, PECAM1, and Rap1b, while the GPIB-IX-V complex was considered to escape the rule. In this investigation, we studied the subcellular localization of GPIb, GPIX, and GPV in the resting platelets of normal subjects, patients with Bernard-Soulier syndrome, patients with Gray platelet syndrome, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 38 publications
4
44
0
2
Order By: Relevance
“…Interestingly, the localization of GPVI in resting platelets was quite similar to that of the major platelet GPs such as GPIb, GPIIb-IIIa and GPIV, with distribution observed not only on the surface plasma membrane but also on the membranes of the OCS and a-granules (Suzuki et al, 1992(Suzuki et al, , 1996aBerger et al, 1993Berger et al, , 1996Wencel-Drake et al, 1993;Nurden et al, 1994Nurden et al, , 1996Nurden et al, , 1999. In the present study, the rate of intracellular distribution of GPVI was estimated to be 35AE4 ± 3AE2% (mean ± SD) of the total and may be larger than that of GPIIb-IIIa (Woods et al, 1986).…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, the localization of GPVI in resting platelets was quite similar to that of the major platelet GPs such as GPIb, GPIIb-IIIa and GPIV, with distribution observed not only on the surface plasma membrane but also on the membranes of the OCS and a-granules (Suzuki et al, 1992(Suzuki et al, , 1996aBerger et al, 1993Berger et al, , 1996Wencel-Drake et al, 1993;Nurden et al, 1994Nurden et al, , 1996Nurden et al, , 1999. In the present study, the rate of intracellular distribution of GPVI was estimated to be 35AE4 ± 3AE2% (mean ± SD) of the total and may be larger than that of GPIIb-IIIa (Woods et al, 1986).…”
Section: Discussionmentioning
confidence: 74%
“…Two previous studies found a small increase in GPIba expression on PRP-PC platelets immediately after preparation which subsequently fell (Bode, 1990;Michelson et al, 1988). Whether this represents a redistribution of GPIba from intracellular pools (Berger et al, 1996), as suggested by Michelson (1988), or whether it is an artefact of the analysis, is unclear. Both groups reported the simultaneous appearance of a GPIba-negative population, and exclusion of these platelets from the flow cytometric analysis could give an apparent rise in the overall level of GPIba per platelet in the residual GPIba-positive population.…”
Section: Discussionmentioning
confidence: 92%
“…Studies performed on the platelets of a patient with type I Glanzmann's thrombasthenia also confirmed that VnR distribution was not influenced by the presence of GP IIb-IIIa complexes. It should be noted that Berger et al (1996) recently showed that membranes of a-granules contain GP Ib, GP IIb, GP IIIa, GP IV, GP V and GP IX, and represent a mirror image of the plasma membrane. Our results suggest that VnR should be added to this list.…”
Section: Discussionmentioning
confidence: 99%